2008
DOI: 10.1038/cdd.2008.141
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Silencing of membrane-associated sialidase Neu3 diminishes apoptosis resistance and triggers megakaryocytic differentiation of chronic myeloid leukemic cells K562 through the increase of ganglioside GM3

Abstract: In chronic myeloid leukemia K562 cells, differentiation is also blocked because of low levels of ganglioside GM3, derived by the high expression of sialidase Neu3 active on GM3. In this article, we studied the effects of Neu3 silencing (40-70% and 63-93% decrease in protein content and activity, respectively) in these cells. The effects were as follows: (a) gangliosides GM3, GM1, and sialosylnorhexaosylceramide increased markedly; (b) cell growth and [3 H]thymidine incorporation diminished relevantly; (c) as m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 41 publications
2
35
0
Order By: Relevance
“…We also investigated changes in the expression of genes related to MK maturation/polyploidization: cyclin D1, cyclin D3, and p21. In primary megakaryocytes cyclin D3 is known to be a key driver of endomitotic cell cycling [35], while PMA-induced MK differentiation in K562 cells corresponds to dramatic increases in cyclin D1 and p21 [36]. Consistent with a reduction in cell cycling, we found that SIRT1 silencing resulted in a 130% increase in p21 levels (relative to the non-silencing control) after 3 days of PMA treatment (Fig.…”
Section: Resultssupporting
confidence: 67%
“…We also investigated changes in the expression of genes related to MK maturation/polyploidization: cyclin D1, cyclin D3, and p21. In primary megakaryocytes cyclin D3 is known to be a key driver of endomitotic cell cycling [35], while PMA-induced MK differentiation in K562 cells corresponds to dramatic increases in cyclin D1 and p21 [36]. Consistent with a reduction in cell cycling, we found that SIRT1 silencing resulted in a 130% increase in p21 levels (relative to the non-silencing control) after 3 days of PMA treatment (Fig.…”
Section: Resultssupporting
confidence: 67%
“…BCR-ABL might be competing with ceramides for providing survival abilities to leukemic cells as shown by a study indicating Abl kinase as a negative regulator of Fas-mediated cell death which is a convergent pathway for ceramide signaling [208,209]. In addition to the importance of ceramides, some gangliosides (GM3 in particular here as well) were shown to be potent for inducing megakaryocytic differentiation of CML blasts [210,211]. Moreover, desialylation of some glycoproteins by Neu2, a cytosolic sialidase, might block BCR-ABL/Src signaling [212].…”
Section: Targeting Sphingolipid Metabolism For the Treatment Of Leukementioning
confidence: 99%
“…Sialidase Activity Assay-The sialidase activity that was present in the particulate fraction of the mock and NEU3-silenced CA-TC and GR-TC cells was assayed using [ 3 H]GD1a at pH 3.8 as previously reported (13). One unit of sialidase activity is defined as the amount of enzyme liberating 1 mol product per min.…”
Section: Methodsmentioning
confidence: 99%
“…Real-time RT-PCR-Real-time PCR was performed as previously reported (13). Primer sequences are shown in supplemental Table S1.…”
Section: Methodsmentioning
confidence: 99%